ESTIMATING SYNERGY VALUE AND ASSET GROWTH INCREASES ON MERGER SIMULATIONS OF STATE-OWNED ISLAMIC COMMERCIAL BANKS - Oktora, Benny
The total growth Indonesian Islamic banking assets consisting of Islamic Commercial Banks (BUS), Islamic Business Units (UUS), and Islamic Rural Banks (BPRS) which reached 15.11% CAGR far exceeded the global growth of 5% CAGR. Unfortunately, despite having high asset growth, market share has only reached 5.78% in 2017, which is still below BAPPENAS expectation on the 2015 AKSI Masterplan of 8.3%. One of the difficulties is due to the relatively low business scale. The Islamic Commercial Bank (BUS) as the biggest part of the Islamic banking industry is expected to be the locomotive of growth. The discourse to merge three state-owned Islamic Commercial Banks (BSM, BRIS, and BNIS) has been raised for years. Mergers will create a larger business scale with higher potential asset growth, that will accelerate the market share growth. The objectives of the study are to estimate the potential of synergy value and asset growth increases. Financial data for the 2014-2018 period and seven-year multi-scenario projections are used in this quantitative study that applies DCF-FCFE valuation model and PBV. The study resulted in a potential synergy value of IDR 7.76 trillion with a higher PBV ratio of 1.95x and a higher potential asset growth of 13.12% CAGR with an upward trend. These positive results should be followed up by the government as their ultimate shareholder, to support accelerating the Indonesian Islamic banking assets growth.